Answer:
![-2 -√(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/gi132yrfbok9sxyz1rwpn4npo11w5xq251.png)
Explanation:
First consider numerator
![sin ((7\pi)/(6))/(2) = sin (7\pi)/(12)= sin ((\pi)/(4) + (\pi)/(3))](https://img.qammunity.org/2022/formulas/mathematics/high-school/ym6ewqxfjw493lxto6corbb7bgc8i3da1h.png)
Using the formula : sin (A + B) = sin A cos B + cos A sin B
![sin (\pi)/(4) = (√(2) )/(2), \ cos (\pi)/(4) = (√(2) )/(2)\\\\sin (\pi)/(3) = (√(2) )/(2), \ cos (\pi)/(3) = (1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/h3fwkwxg6mwvilhgrc1a0pi0yzh85v26p2.png)
![sin((\pi)/(4) + (\pi)/(3)) = sin (\pi)/(4) \cdot cos (\pi)/(3) + cos (\pi)/(4) \cdot sin (\pi)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/bebelcqmrlxl4jmm2who5xhyiq8o0c3oiw.png)
![=(√(2) )/(2) \cdot (1)/(2) + (√(2) )/(2) \cdot (√(3) )/(2) \\\\= (√(2) )/(4) + (√(6) )/(4)\\\\=(√(2) +√(6) )/(4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/o8aunll37qjk05mlg2iymk1jc749jfx4ii.png)
Second consider denominator
![cos ((7\pi)/(6))/(2) = cos (7\pi)/(12)= cos ((\pi)/(4) + (\pi)/(3))](https://img.qammunity.org/2022/formulas/mathematics/high-school/e51ir95f83qqfvzqqn9wv357a9o4lq2i85.png)
Using the formula : cos (A + B) = cos A cos B - sin A sin B
![sin (\pi)/(4) = (√(2) )/(2), \ cos (\pi)/(4) = (√(2) )/(2)\\\\sin (\pi)/(3) = (√(2) )/(2), \ cos (\pi)/(3) = (1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/h3fwkwxg6mwvilhgrc1a0pi0yzh85v26p2.png)
![cos((\pi)/(4) + (\pi)/(3)) = cos (\pi)/(4) \cdot cos (\pi)/(3) -sin (\pi)/(4) \cdot sin (\pi)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/e3a0s99trgvqu81n1xfjtxewnwbyi0vn0g.png)
![=(√(2) )/(2) \cdot (1)/(2) - (√(2) )/(2) \cdot (√(3) )/(2)\\\\=(√(2))/(4) - (√(6))/(4)\\\\= (√(2) -√(6) )/(4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/rfolg2t5toqujuo3lvx6bj2ehj0gxi0wh0.png)
Therefore,
![tan (7\pi)/(12) = (sin (7\pi)/(12))/(cos(7\pi)/(12))](https://img.qammunity.org/2022/formulas/mathematics/high-school/qswv63g0flb8jgqqwjlys8bz8inxd9tdn1.png)
![= \frac{(√(2) +√(6) )/(4)} {(√(2) -√(6) )/(4) }\\\\=(√(2) +√(6) )/(4) * (4 )/(√(2) -√(6))\\\\=(√(2) +√(6) )/(√(2) -√(6))](https://img.qammunity.org/2022/formulas/mathematics/high-school/q9k8k8wvyd3guar5zwvk29dhv45szvbrt7.png)
Either we can stop here or Rationalize the denominator:
![(√(2) +√(6) )/(√(2) -√(6)) * (√(2) +√(6) )/(√(2) +√(6)) = ((√(2) +√(6))^(2) )/((√(2))^2 -(√(6))^2) = (2 + 6 +2√(12) )/(2-6) = (8+2√(12) )/(-4) = (8+ 4√(3) )/(-4) = -2-√(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/vhb7sx3oazv3sdxcfo98lbmyhj6dxtm1yx.png)